The impact of thrombus surface morphology of the basilar artery on the successful rate of mechanical thrombectomy - Jiang, Xinzhao; Yu, Shufeng; Wang, David; Dong, YI; Wang, Peng (Frontiers in Neurology, 2023)
The present study aimed to investigate the impact of angiographic thrombus surface morphology on the angiographic and clinical outcomes of basilar artery occlusion (BAO).This retrospective study included 141 patients with acute BAO who underwent mechanical thrombectomy (MT). We categorized thrombus surface phenotypes as either regular (smooth and straight, either convex or concave) or irregular. Patients with BAO were grouped based on the presence of a regular or irregular phenotype, and we compared their angiographic and clinical outcomes.In total, 52.5% (74/141) of acute BAO patients exhibited a regular thrombus morphology. These patients had a higher rate of first-pass effect (28.4% vs 4.5%, P = 0.0002), and fewer retrieval attempts (2 vs 2; P = 0.0198) compared to those with an irregular morphology. Among patients treated with contact aspiration (CA), the regular thrombus morphology showed a higher first-pass success rate (45.7% vs. 12.8%; p = 0.0017), a shorter procedural duration (46 vs. 50 minutes; p = 0.0159), and fewer retrieval attempts (1 vs. 2; p = 0.0338) compared to stent retriever (SR) thrombectomy.Both the regular thrombus morphology (OR 7.72, 95% CI 2.02 -29.52; p = 0.003) and using CA as the first-line treatment (OR 3.37, 95% CI 1.12 -10.13; p = 0.031) independently predicted first-pass success.For BAO patients treated with CA as the primary strategy, the presence of a regular thrombus surface might predict higher first-pass success and shorter procedural duration. Diligent assessment of thrombus morphology within the MT workflow could improve the feasibility of procedural techniques.